Effect of cooling rate on microstructure of B2-NiSc intermetallics - Yuan, Zhipeng (Array, 2019)
Ni-50at%Sc alloy was prepared by centrifugal casting method. Volume fraction, the actual content of B2-NiSc and second phase Ni2Sc in alloy were analyzed with an Image-Pro Plus software. The cooling rates for the solidified thin plate with thickness of 2.65mm, 1.2mm, 0.75mm and 0.35 mm are 1164, 2570, 4112 and 8811 K·s1, respectively. It is found that d=0.5 mm was an critical dimension which corresponds to an abrupt change in the solidification rate. It is also found that (Ni2Sc+NiSc)eutectic was dispersed at grain boundary or between dendritic arms due to the loss of Sc element during melting. While d＞0.5mm (corresponding to the thin plate with thickness of 0.75mm, 1.20mm and 2.65 mm), the solidification structure consists of primary phase B2-NiSc and (Ni2Sc+NiSc)eutectic. While d ＜ 0.5mm (corresponding to the thin plate with thickness of 0.35 mm), the solidification structure is composed of fine globular B2-NiSc and relatively small amounts of (Ni2Sc+NiSc)eutectic. Based on the phase volumetric analyzing of the microstructure with an Image-Pro Plus software, the loss of Sc element during melting was about 3.01~3.10 at%. The eutectic NiSc in the lamellar eutectic structure together with the primary phase B2-NiSc form a larger single phase NiSc, while Ni2Sc with the form of particles is distributed on the grain boundaries after (970 ℃, 72 h) homogenization heat treatment.